Examining Moral Reasoning and Transactional Leadership behaviour in the Nigerian Public Sector - Felix, Chikelu Okey; ., Rosita Bint Arshad (Journal of Economics and Behavioral Studies, 2015)
The relationship between moral reasoning and leadership style has received considerable attention for decades, however this has been not fully explicated as different leadership styles elist different ethical values. What constitutes moral behaviour is conflicting and subjective. This study examines public leaders’ degree of moral judgment associated with leadership styles in a public sector organization. To test the hypothesized relationship, data were collected using questionnaire survey distributed to 550 workers out which 300 were found worthy to be used. The Defining Issues Test (DIT2) and the Multifactor leadership questionnaire (MLQ X5) were completed by leaders and subordinates respectively. The PLS path analysis of the structural model indicates significant statistical relationship between cognitive moral development (CMD) and transactional leadership style (TSL) ( β= -0.214, P< 0.012). However, we argue that cognitive moral development is amiable to the individual qualities of the leader that might necessitate the application of particular leadership style and behaviour. We also found collaboration evidence that leaders high in cognitive moral development are perceived more as transformational leaders by their subordinates. Finally, we suggest that the dichotomies between moral reasoning and leadership style are hinged more on individual leadership values and motivational beliefs.